Traditional Uses, Bioactive Compounds, and Pharmacological Investigations of Calendula arvensis L.: A Comprehensive Review - Aya Khouchlaa; Aicha El Baaboua; Hamza El Moudden; Fatima Lakhdar; Saad Bakrim; Naoual El Menyiy; Omar Belmehdi; Hicham Harhar; Nasreddine El Omari; Abdelaali Balahbib; Moon Nyeo Park; Gokhan Zengin; et al. (Advances in Pharmacological and Pharmaceutical Sciences)
Calendula arvensis L. (Asteraceae) is a famous ornamental and medicinal plant widely distributed in Mediterranean countries and the southern region of Europe. This reputed species is widely used in traditional medicine in the treatment of many disorders and has various bioactivities, especially anti-inflammatory, antiviral, antimutagenic, antimicrobial, insecticidal, antioxidant, and immunomodulatory activities. The present review was conducted to provide a critical review of the comprehensive and current knowledge regarding C. arvensis species, in particular, its taxonomy and geographical distribution, botanical description, medicinal uses, phytochemical compounds, pharmacological properties, and toxicity investigations. The data collected on C. arvensis were obtained using different scientific research databases such as PubMed, SciFinder, SpringerLink, Web of Science, Science Direct, Google Scholar, Wiley Online, and Scopus. Phytochemical screening of different C. arvensis extracts and essential oils showed their richness in bioactive compounds, particularly in fatty acids, sterols, phenolics, flavonoids, saponins, tannins, alkaloids, and terpenoid compounds. The findings of this review showed that the pharmacological activities of C. arvensis confirm its importance and diversity as a traditional remedy for many diseases. This plant presents a wide range of bioactivities, namely, anti-inflammatory, antimicrobial, antitrypanosomial, antitumoral, antimutagenic, and immunomodulatory activities, as well as hemolytic properties and wound treatment. Nevertheless, pharmacokinetic validation and toxicological examinations are required to detect any possible toxicity for future clinical trials.